Isolation and characterisation of irinans, androstane-type withanolides from Physalis peruviana L. - Stein, Annika; Compera, Dave; Karge, Bianka; Brönstrup, Mark; Franke, Jakob (Beilstein Journal of Organic Chemistry, 2019)
Withanolides are steroidal lactones widespread in Nightshade plants with often potent antiproliferative activities. Additionally, the structural diversity of this compound class holds much potential for the discovery of novel biological activity. Here, we report two newly characterised withanolides, named irinans, from Physalis peruviana with highly unusual truncated backbones that resemble mammalian androstane sex hormones. Based on biomimetic chemical reactions, we propose a model that links these compounds to withanolide biosynthesis. Irinans have potent antiproliferative activities, that are however lower than those of 4ß-hydroxywithanolide E. Our work establishes androwithanolides as a new subclass of withanolides.
Keywords: androstanes; Physalis peruviana; steroids; structure elucidation; withanolides

(untitled) - Rai, M.; Jogee, P. S.; Agarkar, G.; Santos, C. A. d. (Pharm. Biol. (Abingdon, U. K.), 2016)

(untitled) - Maurya, R. (J. Pharm. Pharmacol., 2010)

(untitled) - Chen, L.-X.; He, H.; Qiu, F. (Nat. Prod. Rep., 2011)

Postharvest Biology and Technology of Tropical and Subtropical Fruits - Fischer, G.; Herrera, A.; Almanza, P. J. (Cape Gooseberry (Physalis Peruviana L.), 2011)

(untitled) - Sang-ngern, M.; Youn, U. J.; Park, E.-J.; Kondratyuk, T. P.; Simmons, C. J.; Wall, M. M.; Ruf, M.; Lorch, S. E.; Leong, E.; Pezzuto, J. M.; Chang, L. C. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Park, E.-J.; Sang-Ngern, M.; Chang, L. C.; Pezzuto, J. M. (J. Nat. Prod., 2019)

(untitled) - Kirson, I.; Abraham, A.; Sethi, P. D.; Subramanian, S. S.; Glotter, E. (Phytochemistry, 1976)

(untitled) - Frolow, F.; Ray, A. B.; Sahai, M.; Glotter, E.; Gottlieb, H. E.; Kirson, I. (J. Chem. Soc., Perkin Trans. 1, 1981)

(untitled) - Sakurai, K.; Ishii, H.; Kobayashi, S.; Iwao, T. (Chem. Pharm. Bull., 1976)

(untitled) - Neogi, P.; Sahai, M.; Ray, A. B. (Phytochemistry, 1986)

(untitled) - Dinan, L. N.; Sarker, S. D.; Šik, V. (Phytochemistry, 1997)

(untitled) - Fang, S.-T.; Liu, J.-K.; Li, B. (Steroids, 2012)

(untitled) - Ahmad, S.; Malik, A.; Yasmin, R.; Ullah, N.; Gul, W.; Khan, P. M.; Nawaz, H. R.; Afza, N. (Phytochemistry, 1999)

(untitled) - Lan, Y.-H.; Chang, F.-R.; Pan, M.-J.; Wu, C.-C.; Wu, S.-J.; Chen, S.-L.; Wang, S.-S.; Wu, M.-J.; Wu, Y.-C. (Food Chem., 2009)

(untitled) - Fang, S.-T.; Li, B.; Liu, J.-K. (Helv. Chim. Acta, 2009)

(untitled) - Zhang, W.-N.; Tong, W.-Y. (Chem. Biodiversity, 2016)

(untitled) - Xia, G.; Li, Y.; Sun, J.; Wang, L.; Tang, X.; Lin, B.; Kang, N.; Huang, J.; Chen, L.; Qiu, F. (Steroids, 2016)

(untitled) - Xu, Y.-m.; Bunting, D. P.; Liu, M. X.; Bandaranayake, H. A.; Gunatilaka, A. A. L. (J. Nat. Prod., 2016)

(untitled) - Chen, L.-X.; Xia, G.-Y.; He, H.; Huang, J.; Qiu, F.; Zi, X.-L. (RSC Adv., 2016)

(untitled) - Ozawa, M.; Morita, M.; Hirai, G.; Tamura, S.; Kawai, M.; Tsuchiya, A.; Oonuma, K.; Maruoka, K.; Sodeoka, M. (ACS Med. Chem. Lett., 2013)

(untitled) - Zhang, H.; Timmermann, B. N. (J. Nat. Prod., 2016)

(untitled) - Kicman, A. T. (Br. J. Pharmacol., 2008)

(untitled) - Maldonado, E.; Alvarado, V. E.; Torres, F. R.; Martínez, M.; Pérez-Castorena, A. L. (Planta Med., 2005)

(untitled) - Siddiqui, B. S.; Usmani, S. B.; Begum, S.; Siddiqui, S. (Phytochemistry, 1993)

(untitled) - Sanogo, R.; Germano, M. P.; de Tommasi, N.; Pizza, C.; Aquino, R. (Phytochemistry, 1998)

(untitled) - Pupo, M. T.; Vieira, P. C.; Fernandes, J. B.; das G.F. da Silva, M. F.; Fo, E. R. (Phytochemistry, 1997)

(untitled) - Miller, W. L.; Auchus, R. J. (Endocr. Rev., 2011)

(untitled) - Fukushima, A.; Nakamura, M.; Suzuki, H.; Yamazaki, M.; Knoch, E.; Mori, T.; Umemoto, N.; Morita, M.; Hirai, G.; Sodeoka, M.; Saito, K. (Front. Plant Sci., 2016)

(untitled) - Dhar, N.; Razdan, S.; Rana, S.; Bhat, W. W.; Vishwakarma, R.; Lattoo, S. K. (Front. Plant Sci., 2015)

(untitled) - Strushkevich, N.; MacKenzie, F.; Cherkesova, T.; Grabovec, I.; Usanov, S.; Park, H.-W. (Proc. Natl. Acad. Sci. U. S. A., 2011)

Cytochrome P450: Structure, Mechanism, and Biochemistry - Ortiz de Montellano, P. R. (Substrate Oxidation by Cytochrome P450 Enzymes, 2015)

(untitled) - Capon, R. J. (Nat. Prod. Rep., 2019)

(untitled) - Zviely, M.; Goldman, A.; Kirson, I.; Glotter, E. (J. Chem. Soc., Perkin Trans. 1, 1986)

(untitled) - García, N.; Rubio-Presa, R.; García-García, P.; Fernández-Rodríguez, M. A.; Pedrosa, M. R.; Arnáiz, F. J.; Sanz, R. (Green Chem., 2016)

(untitled) - Yen, C.-Y.; Chiu, C.-C.; Chang, F.-R.; Chen, J. Y.-F.; Hwang, C.-C.; Hseu, Y.-C.; Yang, H.-L.; Lee, A. Y.-L.; Tsai, M.-T.; Guo, Z.-L.; Cheng, Y.-S.; Liu, Y.-C.; et al. (BMC Cancer, 2010)

(untitled) - Xu, Y.-M.; Wijeratne, E. M. K.; Babyak, A. L.; Marks, H. R.; Brooks, A. D.; Tewary, P.; Xuan, L.-J.; Wang, W.-Q.; Sayers, T. J.; Gunatilaka, A. A. L. (J. Nat. Prod., 2017)

(untitled) - Ishiyama, M.; Tominaga, H.; Shiga, M.; Sasamoto, K.; Ohkura, Y.; Ueno, K. (Biol. Pharm. Bull., 1996)

(untitled) - Sasse, F.; Steinmetz, H.; Schupp, T.; Petersen, F.; Memmert, K.; Hofmann, H.; Heusser, C.; Brinkmann, V.; Matt, P. V.; Höfle, G.; Reichenbach, H. (J. Antibiot., 2002)